PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF PHYSICAL CULTURE DEVELOPMENT AMONG STUDENTS IN THE CONTEXT OF HIGHER EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the significance of physical education for university students from a psychological and pedagogical perspective. Based on the analysis of scientific and methodological literature, key psychological and pedagogical conditions that contribute to increasing students’ interest in physical culture are identified. The findings of the study can be applied to improve the educational process, enhance students’ motivation for physical activity, and create favorable conditions for their comprehensive physical development.